Global Commodity Price Dynamics On IHSG Return Volatility - Hutahaean, Thomas Firdaus; Hasyim, Sirojuzilam; Syafii , M. (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
The Composite Stock Price Index (IHSG), as the main indicator of the Indonesian stock market, exhibits time-varying volatility that is highly sensitive to external shocks, particularly fluctuations in global commodity prices. This study aims to examine the impact of global gold prices, crude oil prices, and coal prices on the volatility of IHSG returns using the Autoregressive Conditional Heteroskedasticity (ARCH) and Generalized Autoregressive Conditional Heteroskedasticity (GARCH) models. The study employs daily data from January 2015 to December 2024, comprising 2,609 observations. Estimation is conducted using the Maximum Likelihood method under the assumption of normal distribution. The results indicate that, in the mean equation of the GARCH model, global oil prices have a positive and statistically significant effect on IHSG returns, while gold and coal prices do not exhibit significant effects. In the variance equation, both ARCH and GARCH parameters are statistically significant, confirming the presence of volatility clustering and high volatility persistence in the Indonesian stock market. Diagnostic tests based on the ARCH LM procedure reveal no remaining conditional heteroskedasticity in the residuals, indicating that the model is well specified and stable. These findings highlight the dominant role of global oil prices in shaping stock market risk in Indonesia, whereas gold primarily serves as a safe-haven asset and coal exerts a sector-specific influence. This study provides empirical evidence on volatility transmission from global commodity markets to the Indonesian stock market and offers important implications for investors and policymakers in managing market risk.